2020
DOI: 10.1111/vsu.13468
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clipping on bacterial contamination of canine arthrocentesis sites before and after skin preparation

Abstract: Objective: To determine the influence of hair removal as part of the aseptic skin preparation of canine arthrocentesis sites and to characterize the bacterial flora remaining after aseptic skin preparation. Study design: Randomized controlled trial. Study population: Thirteen shorthaired beagle-cross dogs. Methods: A coin toss was used to randomly determine to have one carpus, elbow, tarsus, and stifle clipped. The contralateral side was left unclipped. Aseptic skin preparation was performed on all sites with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Nonetheless, the previous study by Wang et al [20] has found bacterial DNA in normal joints, suggesting that the presence of bacterial DNA may not be specifically associated with arthritis [21]. It is possible that the detected bacteria entered through blood flow to the synovial membrane [22,23].…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, the previous study by Wang et al [20] has found bacterial DNA in normal joints, suggesting that the presence of bacterial DNA may not be specifically associated with arthritis [21]. It is possible that the detected bacteria entered through blood flow to the synovial membrane [22,23].…”
Section: Discussionmentioning
confidence: 91%
“…The position of the needle is particularly important for this type of procedure, so as not to cause lesions in the adjacent tissues, such as arteries, vessels, or nerves, and to access the joint with minimal soft tissue damage. Arthrocentesis is a common intervention for diagnosis or treatment of joint diseases in veterinary practice in small animals and horses (Kearney et al, 2021; Lavallée et al, 2020; Mielke et al, 2018; Watkins et al, 2021). Synovial fluid collection for cytology, bacterial or fungal culture, arthrography, intra‐articular injections of medication such as corticosteroids and anesthetics are some of clinical applications of this procedure (Kearney et al, 2021; Lavallée et al, 2020; Mielke et al, 2018; Pouyet & Bonilla, 2021; Watkins et al, 2021; Whipple et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Arthrocentesis is a common intervention for diagnosis or treatment of joint diseases in veterinary practice in small animals and horses (Kearney et al, 2021; Lavallée et al, 2020; Mielke et al, 2018; Watkins et al, 2021). Synovial fluid collection for cytology, bacterial or fungal culture, arthrography, intra‐articular injections of medication such as corticosteroids and anesthetics are some of clinical applications of this procedure (Kearney et al, 2021; Lavallée et al, 2020; Mielke et al, 2018; Pouyet & Bonilla, 2021; Watkins et al, 2021; Whipple et al, 2019). Other procedures to treat joint diseases such as arthroscopy and arthrotomy can also be performed (Hoelzler et al, 2004; Pouyet & Bonilla, 2021), although for all these interventions it is necessary to know the normal anatomy of the joint to be accessed.…”
Section: Discussionmentioning
confidence: 99%
“…Identified peptide biomarkers to identify botulism in cattle [89] Various organisms Studied how aseptic skin preparation techniques affected bacterial counts prior to surgery [90] Staphylococcus cohnii, Bordetella bronchiseptica, Bordetella parapertussis, Corynebacterium glucuronolyticum, Pelistega suis, and Rodentibacter rarus Screening of deceased street rats in France [91] Staphylococcus pseudintermedius Canine pyoderma, antibiotic resistance [92]…”
Section: Clostridium Botulinummentioning
confidence: 99%
“…In an interesting study of clinical veterinary relevance, Lavallee et al [90] used MALDI-TOF to study the microbiome of canine arthrocentesis sites. The authors focused on how aseptic skin preparation techniques affected bacterial counts, and whether clipping the animals' hair before the procedure affected results.…”
Section: Streptococcus Salivarius Streptococcus Equinus Andmentioning
confidence: 99%